Comparative Study of Molasses and Chemical Retarders on Concrete Compressive Strength and Setting Time - Bali, Ika; Matondang, Imanuel (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2025)
Concrete damage is often linked to reduced structural strength due to rapid setting, which complicates compaction and placement. Chemical retarders are commonly used to address this issue but are costly and environmentally unfriendly. Molasses, a by-product of the sugar industry containing sucrose, glucose, and fructose, offers a potentially eco-friendly and economical alternative. This study compares the effects of molasses and a chemical retarder (Plastiment VZ) at dosages of 0.2–0.4% on concrete compressive strength and initial setting time. Results show that 0.35% molasses increased compressive strength to 25.48 MPa compared to 19.53 MPa in normal concrete, though strength declined at 0.4%. Plastiment VZ showed more consistent gains, reaching 25.90 MPa at 0.4%. For setting time, molasses delayed hydration to 435 minutes (0.4%), while Plastiment VZ extended it further to 690 minutes (0.4%). Thus, molasses can serve as an alternative retarder, though Plastiment VZ provides more stable effects.